New Brazilian species of Furculanurida Massoud, 1967 (Collembola: Neanuridae) - Queiroz, Gabriel C.; Fernandes, Liliane H. (Zootaxa, 2011)
Furculanurida tropicalia sp. nov., is described from leaf litter of the Atlantic forest of Southeast Brazil. It is characterized as being the first species of the genus that possess 8+8 eyes. New diagnosis and remarks on the genus and the species of Furculanurida are made. The species Stachorutes arlei is transferred once more from Furculanurida to Stachorutes.